2012
DOI: 10.3189/2012jog12j020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of model resolution on simulated wind, drifting snow and surface mass balance in Terre Adélie, East Antarctica

Abstract: ABSTRACT. This paper presents the impact of model resolution on the simulated wind speed, drifting snow climate and surface mass balance (SMB) of Terre Adélie and its surroundings, East Antarctica. We compare regional climate model simulations at 27 and 5.5 km resolution for the year 2009. The wind speed maxima in Terre Adélie and the narrow glacial valleys of Victoria Land are better represented at 5.5 km resolution, because the topography is better resolved. Drifting snow sublimation is >100 mm a −1 in regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 33 publications
2
46
1
Order By: Relevance
“…However, based on data obtained from a regional atmospheric climate model, RAMCO 2.1/ANT, with a spatial resolution of approximately 27 km, a recently published paper by Lenaerts et al (2012a) showed that the inter-annual variability of drifting snow sublimation integrated over the ice sheet is small (approximately 12 Gt yr −1 ) at only approximately 0.5 % of the total accumulation. Conversely, Lenaerts et al (2012b) demonstrated that the increase in the RAMCO2.1/ANT model resolution from 27 to 5.5 km can improve the model's ability to forecast the wind speed maxima in Adélie Land. As a result, the SMB exhibits a much greater local spatial variability at a 5.5 km resolution, an effect controlled by drifting snow erosion, and the blowing snow sublimation is > 100 kg m −2 yr −1 in regions with high wind speeds.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on data obtained from a regional atmospheric climate model, RAMCO 2.1/ANT, with a spatial resolution of approximately 27 km, a recently published paper by Lenaerts et al (2012a) showed that the inter-annual variability of drifting snow sublimation integrated over the ice sheet is small (approximately 12 Gt yr −1 ) at only approximately 0.5 % of the total accumulation. Conversely, Lenaerts et al (2012b) demonstrated that the increase in the RAMCO2.1/ANT model resolution from 27 to 5.5 km can improve the model's ability to forecast the wind speed maxima in Adélie Land. As a result, the SMB exhibits a much greater local spatial variability at a 5.5 km resolution, an effect controlled by drifting snow erosion, and the blowing snow sublimation is > 100 kg m −2 yr −1 in regions with high wind speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Reanalysis have been largely used to estimate climatic conditions and the Antarctic SMB (e.g., Monaghan et al, 2006;Genthon et al, 2005;Agosta et al, 2012), as well as to force regional circulation models (e.g., Van de Berg et al, 2006;Lenaerts et al, 2012a;Gallée et al, 2013). The reanalysis methodology is based on assimilating meteorological observations (e.g., Bromwich et al, 2011), which provides more reliable outputs than classical atmospheric models.…”
Section: Available Smb Data From Era-interim Reanalysismentioning
confidence: 99%
“…The model used for ERA-Interim does not account for wind erosion or deposition processes (ER). Snow drift and wind processes are expected to have significant effects on SMB when wind speed is high (e.g., Gallée et al, 2013;Lenaerts et al, 2012a). These processes introduce a major uncertainty in SMB computations by ERA-Interim in low elevation areas.…”
Section: Available Smb Data From Era-interim Reanalysismentioning
confidence: 99%
“…One-dimensional (1-D) numerical models have been compared with aeolian snow transport rates in ideal cases (Xiao et al, 2000) and with observations (Lenaerts et al, 2010). Regional climate models have been evaluated against surface mass balance estimates derived from stake networks Lenaerts et al, 2012c). The latter is an integrative method that includes all the components of the surface mass balance: precipitation, run-off, surface and windborne snow sublimation, and erosion/deposition of snow.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is an integrative method that includes all the components of the surface mass balance: precipitation, run-off, surface and windborne snow sublimation, and erosion/deposition of snow. Aeolian snow transport events simulated by regional climate models have been compared with remote sensing techniques (see Palm et al, 2011), and with visual observations at different polar stations (Lenaerts et al, 2012b) or with particle impact sensors (Lenaerts et al, 2012c). Aeolian snow mass flux measurements are even rarer.…”
Section: Introductionmentioning
confidence: 99%